Mental disorders and community care : a discourse analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Danks, Josephine Helen (Massey University, 1995)
Talk about people with mental disorders and community care was examined using Potter and Wetherell's (1987) system of discourse analysis. Participants were ten members of the public, resident in a suburban community. They were interviewed on the topics of community care policy, rights, responsibility and care, the location of community residences, and general knowledge about people with mental disorders. Verbatim transcripts from interviews were analysed, and six interpretive repertoires identified, these being, rights promotion, dual community, patronisation, affiliation, solicitous control and disorder repertoires. While participants' talk often contained content indicating support and concern for people with disorders, the repertoires were constructed in a way which functioned to promote and protect their own interests. Analysis of linguistic devices revealed how participants used language to distance themselves from socially unacceptable talk, and claim consensus for their views. The social consequences of discourse constructed in the form used by participants was discussed. Overall the analysis suggested that the way ordinary members of the public talk about people with mental disorders and their care in the community has a negative influence on the social interaction between the two.
Keywords: Mental health services, New Zealand; Community care; Perceptions of mentally ill